Near-Coincident Indicators of Systemic Stress - Arsov, Ivailo (IMF Working Papers; Working Paper ;, 2013)
The G-20 Data Gaps Initiative has called for the IMF to develop standard measures of tail risk, which we identify in this paper with systemic risk. To understand the conditions under which tail risk is present, it is first necessary to develop a measure of what constitutes a systemic stress, or tail, event. We develop such a measure and uses it to assess the performance of eleven near-term systemic risk indicators as 'early' warning of distress among top financial institutions in the United States and the euro area. Two indicators perform particularly well in both regions, and a couple of other simple indicators do well across a number of criteria. We also find that the sizes of institutions do not necessarily correspond with their contribution to spillover risk. Some practical guidance for policies is provided.